KONSTRUKSI BERITA OLAHRAGA PADA MEDIA MASSA INTERNET (ANALISIS FRAMING BERITA KONFLIK MARQUEZ DAN ROSSI PADA SINDONEWS.COM - Armaiga Chandra; Belli Nasution (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
The Internet as a mass media managed to change the human form, from local to global, open to the development of information, to influence their civilization and dubbed the big village, which is a big village. They can get to know each other and greet each other. In this study, SINDOnews.com is an internet mass media site that has a tagline, "Trusted Source of Information".At the end of 2015, there was a conflict between Marquez and Rossi. Their feud at that time became a warm conversation in various circles. SINDOnews, as one of the sites that preach the conflict will be analyzed, about how the site in preaching about the conflict between Marquez and Rossi. By the methods of Zhongdang Pan and Gerald M. Kosicki, the news about their conflict will be constructed.There are six news analyzed, and the result SINDOnews.com tend to make news by cornering the Marquez. Many inappropriate opinions are mixed up in the news. One of his opinions was "the organizers are considered to have acted arrogantly by not imposing sanctions on Marc Marquez". The opinion is in a story entitled, "Nothing Can Prohibit Marquez Provocation Rossi". With the addition of the word "arrogant", and no facts that support the news, it is clear that it is merely an opinion that cornered the MarquezKeywords : SINDOnews.com, mass media, framing